Ultrastructural studies of sensilla in one fly of forensic importance - Carriço, Cesar; Caetano, Rebecca Leal; Nascimento, Thalyta Maria de Souza; Pinto, Zeneida Teixeira (EntomoBrasilis, 2020)
Taxonomic identification is essential in the field of forensic entomology. Insects are important in the decomposition of cadavers. The flies are generally attracted to cadavers and one of the most important contributions is to estimate the postmortem interval. The scanning electron microscopy (SEM), which allows rapid and accurate identification of different species of forensics flies, has been highlighted as it allows better visualization of the external morphology of immature and some adults. The purpose of this study was to examine in details the morphological aspects of sensilla on the antennae of female and male of Xanthacrona bipustulata Wulp using SEM, since many of them could not be observed just by the use of light microscopy.